Pengaruh Current Ratio, Debt To Quity Dan Total Asset Turnover Ratio Terhadap Return On Asset Pada Perusahaan Kimia Yang Terdaftar Di Bursa Efek Indonesia - Sukma Nur Wahyudi (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research aims to analyze the influence of Current Ratio, Debt to Equity Ratio, and Total Asset Turnover on Return on Assets in chemical companies listed on the Indonesia Stock Exchange (BEI). The data used in this research is secondary data obtained from the financial reports of chemical companies listed on the IDX during the 2020-2023 period. The analytical method used is multiple linear regression. The research results show that the Current Ratio, Debt to Equity Ratio, and Total Asset Turnover simultaneously have a significant effect on Return On Assets. Partially, the Current Ratio and Total Asset Turnover have a positive and significant effect on Return On Assets, while the Debt to Equity Ratio has a negative and significant effect on Return On Assets